Development of a 3D Tissue‐Engineered Skeletal Muscle and Bone Co‐culture System. Issue 1 (20th September 2019) - Wragg, Nicholas M.; Mosqueira, Diogo; Blokpeol‐Ferreras, Lia; Capel, Andrew; Player, Darren J.; Martin, Neil R. W.; Liu, Yang; Lewis, Mark P.
Abstract: In vitro 3D tissue‐engineered (TE) structures have been shown to better represent in vivo tissue morphology and biochemical pathways than monolayer culture, and are less ethically questionable than animal models. However, to create systems with even greater relevance, multiple integrated tissue systems should be recreated in vitro. In the present study, the effects and conditions most suitable for the co‐culture of TE skeletal muscle and bone are investigated. High‐glucose Dulbecco's modified Eagle medium (HG‐DMEM) supplemented with 20% fetal bovine serum followed by HG‐DMEM with 2% horse serum is found to enable proliferation of both C2C12 muscle precursor cells and TE85 human osteosarcoma cells, fusion of C2C12s into myotubes, as well as an upregulation of RUNX2/CBFa1 in TE85s. Myotube formation is also evident within indirect contact monolayer cultures. Finally, in 3D co‐cultures, TE85 collagen/hydroxyapatite constructs have significantly greater expression of RUNX2/CBFa1 and osteocalcin/BGLAP in the presence of collagen‐based C2C12 skeletal muscle constructs; however, fusion within these constructs appears reduced. This work demonstrates the first report of the simultaneous co‐culture and differentiation of 3D TE skeletal muscle and bone, and represents a significant step toward a full in vitro 3D musculoskeletal junction model. Abstract : Laboratory‐based 3D models of individual tissues have been shown to better represent native tissue than single layer cell culture. In this study, the conditions to form both skeletal muscle and bone constructs are demonstrated. Indicators of osteogenic differentiation are found to increase in the presence of skeletal muscle. In contrast, skeletal muscle myogenesis is reduced.